Theophylline Revisited. Mechanisms, Challenges, and New Horizons - Szarłowicz, Jakub; Mazur, Michał; Waz, Dorota; Goliszek, Zofia; Sobek, Karolina Łucja; Tabin-Barczak, Wiktoria; Sokołowska, Aldona; Fikas, Klaudia; Chwaliszewski, Kamil; Samuła, Sebastian (Quality in Sport, 2025)
Introduction and Purpose Theophylline, used for over a century in asthma and COPD treatment, provides anti-inflammatory and bronchodilatory effects via phosphodiesterase inhibition and adenosine receptor antagonism. This review examines its mechanisms, clinical uses, and emerging applications. Materials and Methods A detailed analysis of 23 peer-reviewed studies from scientific databases, including PubMed, focused on theophylline’s pharmacokinetics, pharmacodynamics, clinical safety, and novel applications in areas such as immunomodulation, metabolic disorders, and regenerative medicine. Results Theophylline shows anti-inflammatory effects, mitochondrial support, and modulation of key pathways (e.g., PI3K/Akt, NF-κB). It demonstrates potential in COVID-19-related ARDS, promoting muscle regeneration, and treating infertility. However, its narrow therapeutic index and variability in pharmacokinetics remain significant challenges. Conclusion Theophylline remains a cost-effective option in asthma and COPD and shows promise in broader applications like immunomodulation and metabolic disorders. Further research and advanced drug formulations are needed to enhance its safety and therapeutic potential.